Musykilat al-Izdiwajiyah al-Lughawiyah fi Ta’lim al-Lughah al-Arabiyah li al-Natiqina bi Ghairiha fi al-Ma’ahid al-Ta’limiyah bi Afrika / Problems of Bilingualism in Teaching Arabic to Non-Native Speakers in Educational Institutes in Africa - Ahmad Garba; Hamzah Hamzah; Basri Mahmud; Musa Amin Musa (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
Classical Arabic is not just a language among languages, but rather a cultural identity for the Arab community and a religious identity for the Islamic community all over the world from east to west. Classical Arabic today lives in the midst of a turbulent colloquial jungle and is fighting a legitimate war of survival despite the challenges it faces, especially when people are saturated with colloquial culture, live it and admire it. Many of the colloquial speakers find it easy and convenient for them, so they turn to it, use it and interact with it and think that they can do without Classical Arabic. Therefore, they live in a state of cultural schizophrenia and live in a state of linguistic duality. Bilingualism appeared in the Arabic language after the Arab-Islamic conquest, which led to the conversion of many nations and peoples to Islam, and this led to a conflict between the Arabic language and other languages. This paper aims to shed light on the issue of linguistic duality in the Arabic language between Classical and colloquial, and the extent of its problems in education. The researcher used the descriptive method; This is done by following up on scientific materials on the nature of duality at the linguistic level first, and stating the problems that arise at the theoretical level, then addressing the most important factors that led to its emergence, as the study concluded that duality of language came from two main axes; an internal axis, which is the absence of the role of Arabic literature in society, as well as the spread of colloquial language in the field of education, which are the two elements that paved the way for intellectual and cultural colonialism from an external axis to limit the role of classical Arabic in Arab society in particular and Islamic society in general, and this paper contains the nature of linguistic duality, a brief historical overview, the spread of its use in educational institutes in Africa, its problems in teaching the Arabic language and other appropriate axes.المستخلص: إن اللغة العربية الفصحى ليست مجرد لغة بين اللغات، بل هي هوية ثقافية للمجتمع العربي وهوية دينية للمجتمع الإسلامي في كل أنحاء العالم من شرقه إلى غربه. تعيش اللغة العربية الفصحى اليوم وسط غابة عامية مضطربة وتخوض حرب بقاء مشروعة رغم التحديات التي تواجهها، خاصة عندما يتشبع الناس بالثقافة العامية ويعيشونها ويعجبون بها، وكثير من أهل العامية يجدونها سهلة وميسرة لهم، فيتجهون إليها ويستخدمونها ويتفاعلون معها ويظنون أنهم يستطيعون الاستغناء عن العربية الفصحى، لذلك يعيشون في حالة انفصام ثقافي ويعيشون في حالة ازدواجية لغوية. ظهرت الثنائية اللغوية في اللغة العربية بعد الفتح العربي الإسلامي، مما أدى إلى دخول العديد من الأمم والشعوب في الإسلام، وأدى ذلك إلى صراع بين اللغة العربية واللغات الأخرى. تهدف هذه الورقة تسليط الضوء على قضية الازدواجية اللغوية في اللغة العربية بين الفصحى والعامية، ومدى إشكالياتها في التعليم، وقد استخدم الباحث المنهج الوصفي؛ وذلك من خلال متابعة المواد العلمية حول ماهية الازدواجية على المستوى اللغوي أولاً، وبيان الإشكاليات التي تنشأ على المستوى النظري، ثم التطرق إلى أهم العوامل التي أدت إلى ظهورها، حيث خلصت الدراسة إلى أن إزدواجية اللغة جاءت من محورين رئيسيين؛ محور داخلي وهو غياب دور الأدب العربي في المجتمع، وكذلك انتشار العامية في مجال التعليم، وهما العنصران اللذان مهدا الطريق للاستعمار الفكري والثقافي من محور خارجي للحد من دور العربية الفصحى في المجتمع العربي بشكل خاص والمجتمع الإسلامي بشكل عام، وتحتوي هذه الورقة على ماهية الازدواجية اللغوية، ونبذة تاريخية موجزة، وانتشار استخدامها في المعاهد التعليمية في أفريقيا، وإشكالياتها في تعليم اللغة العربية وغيرها من المحاور المناسبة.